FRI0311 The Influence of Rituximab and TOCILIZUMAB Treatment on B-Cell Subsets in Patients with Rheumatoid Arthritis. (10th June 2014) - Suponitskaya, E.; Aleksankin, A.; Avdeeva, A.; Aleksandrova, E.; Novikov, A.; Nasonov, E.
Abstract : Background: B-cell monitoring has been extensively used in patients (pts) with rheumatoid arthritis (RA) to assess the efficacy of biologic therapy and the relationship between B-cell recovery and clinical outcomes. Objectives: To evaluate the B-cell subsets in peripheral blood of RA pts treated with rituximab (RTX) and tocilizumab (TCZ). Methods: 18 pts with active refractory RA were assessed at baseline and at weeks 12 and 24 for clinical and laboratory data. 10 pts: 8F/2M; median age 58 years (47-62); disease duration 6 years (3-20) received RTX and 8 pts: 6F/2M, median age 45.5 years (38-61); disease duration 14 years (7-19) – TCZ in the standard therapeutic dosage. Pts of both groups were treated with DMARDs, glucocorticoids, and NSAIDS. At baseline, DAS28 was 5.1 (4-5.8) and 5.5 (5.2-6.5); 90% (9 pts) and 62.5% (8 pts) were both RF and anti-CCP positive in RTX and TCZ group, respectively, with no difference between the groups. CD19+ B cells, memory B cells (CD19+CD27-), non-switched (CD19+IgD+CD27+) and switched memory B cells (CD19+IgD-CD27+), naïve (CD19+IgD+CD27-), transitional (CD19+IgD+CD10+CD38++CD27-) B cells, and plasmablasts (CD19+CD38+++IgD-CD27+CD20) were analyzed using multicolor flow cytometry. Results: At baseline, the median percentages of memory B cells (CD19+CD27-) and non-switched memory B-cells (CD19+CD27+IgD+) were lower in RA cohort compared to healthy donors (n=27): 1.55% (1.1-2.1) versus 2.2% (1.6-3.3), p=0.028 and 6.2% (2.7-11.1) versus 10% (6.4-12.7), p=0.035, respectively. The percentage of memory B cells (CD19+CD27-) correlated positively (r=0.52) with ESR and negatively (r=-0.49) with the age of the patients, p<0.05 for both cases. There was no difference in the frequencies of B-cell subsets between RTX and TCZ group. At 12 and 24 weeks, DAS28 decreased significantly in RTX group, median 3.2 (2.7-4.2) and 3.4 (2.7-4.1) and TCZ group, median 4.2 (3.5-4.7) and 3.1 (2.9-3.5), p<0.05 for all cases. In RTX group, the complete depletion of CD19+ B cells and memory B cells was seen in all but 1 patient at 12 and 24 weeks. At week 24 of RTX treatment, repopulation occurred mainly with switched memory B cells, median 11.8% (0-31), non-switched, median 1.85% (0-8.15), and naïve B cells, median 3.05% (0-17.5). In TCZ group, the frequency of CD19+ B cells and memory B cells remained stable (median 5.3% (2.5-7.6) and 1.4% (1.2-1.6) at baseline, 3.9% (2.9-7.1) and 1.6% (1.2-1.9) at week 12, 4.2% (3.3-5.3) and 1.1% (0.8-1.1) at week 24, respectively). Transitional cells decreased from a median 0.1%, (0.05-0.1) at baseline to a median 0%, (0-0), p=0.043 after week 12; other B-cell subsets have not changed during the study. Conclusions: The decreased frequencies of memory B cells (CD19+CD27-) and non-switched memory B cells (CD19+CD27+IgD+) were found in RA patients compared to healthy donors. RTX induced a profound depletion of all peripheral CD 19+ B-cell subsets in RA patients. During TCZ therapy, the frequencies of transitional cells decreased at week 12. No significant influence of TCZ was found on other B-cell subsets. Acknowledgements: The authors thank Prof. H.-P. Tony, A. Koss-Kinzinger, and Z. Mahmood (University of Wuerzburg, Germany) for the assistance in the analysis of preliminary results. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3283